Comparing the effectiveness of self-efficacy education and education based on acceptance and commitment on test anxiety and belonging to school in the second high school boys of Birjand city - Javadi, Seyyed Vahid; Ghanifar, Mohammad Hasan; Shahabi Zadeh, Fatemeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Nowadays, education and learning are the most basic activities of life in progressive societies, and the survival and durability of any society depends on acquiring information and applying it in life. The purpose of this research was to compare the effectiveness of self-efficacy education and education based on acceptance and commitment on test anxiety and belonging to school in second secondary school boys in Birjand city. Methods: The current research was a quasi-experimental type that was implemented with a pre-test-post-test design and a 3-month follow-up. Among the second secondary schools in Birjand city, one school was randomly selected and using G Power software, a sample size of 78 students was considered and the students were randomly divided into three groups (26 students in each group) Self-efficacy test, 26 people were included in the ACT intervention group and 26 people were in the control group. The data were analyzed with repeated measures analysis of variance. Results: The findings of the present study showed that self-efficacy training and training based on acceptance and commitment reduce test anxiety and increase the level of belonging to the school of students compared to the control group (p<0.001). The results of the Bonferroni test showed that there was no significant difference between the influence of self-efficacy training compared to training based on acceptance and commitment on test anxiety and belonging to school (p<0.05). Conclusion: Considering the influence of self-efficacy training and education based on acceptance and commitment on test anxiety and belonging to school in students, counselors and therapists can use these approaches to reduce test anxiety and also increase the level of belonging to school.